The role of FIFA World Cup Qatar 2022 brand ambassador: An analysis of Ghanim Al Muftah in promoting inclusive engagement - Rizana, Aulia Holaw; Lisnarini, Naurah (Universitas Ahmad Dahlan, 2023)
Many ways exist to promote and increase awareness of products, one of which is through collaboration with celebrities or well-known figures to become brand ambassadors. Collaboration with brand ambassadors is a form of communication carried out by a brand or event to convey messages and information to the audience regarding the content of the message. This research was conducted with the aim of understanding the role of Ghanim Al Muftah as a brand ambassador in introducing the inclusive FIFA World Cup 2022. The research method used was descriptive qualitative, employing a case study and literature review method. The results obtained in this study show that Ghanim Al Muftah's role as a brand ambassador has garnered a positive response, had a beneficial impact, and effectively conveyed awareness of the inclusivity aspect to the audience.